Novoveški tiski in vezave v Nadškofijskem arhivu Maribor - Urlep, Lilijana (Knjižnica, 2018)
Purpose: The paper presents (early) modern prints from the historical library of the Lavantine bishops, kept at the Archdiocesan Archives Maribor. Modern prints are presented from the thematic, aesthetic, and historical point of view. A general overview is complemented by presentations of individual prints that show specific characteristics. The paper also provides new insights into the history of the historical library and the role of the Lavantine bishops in the creation of the library collection. Methodology/approach: The paper was created using mainly the historical method, based on a critical review of archival resources and library material. Results: The historical library of the Lavantine bishops includes numerous modern prints that can be classified as important monuments of written cultural heritage on the Slovenian and European soil. Modern prints are very diverse in their content. Theological works, led by bibles and liturgical books, prevails. Theology is followed by other humanistic disciplines. Works that stand out because of their content characteristics, rarity (court yearbook dating from 1705), aesthetic qualities with decorative elements and decorative bindings (The Salzburg Missal from 1515 with dated binding), historical or ecclesiastical historical features (The Roman Missal or Lectionary dating from 1761), or because of the combination of all these factors are particularly valuable. A group of liturgical books from the 17th and 18th centuries with decorative bindings is also interesting. Research limitations: Due to diversified workload and lack of time, the prints have not yet been inventoried or catalogued, so it was not possible to provide specific data and to perform statistical analyses. Originality/practical implications: The first study that deals with this topic and serves as a basis for further research.
Keywords: cerkvena zgodovina; cerkvene knjižnice; church libraries; cultural history; ecclesiastical history; knjižnične zbirke; kulturna zgodovina; lavantinska škofija; library collections; modern prints; novoveški tiski; the Diocese of Lavant